Jože Žohar - Maver, Igor (Acta neophilologica, 2019)
The article discusses the verse written by Jože Žohar, the recently deceased and forgotten Slovenian poet migrant poet from Australia. The poet despite his not enormous poetic output shows a prodigious gift for poetic experimentation and tries to reconcile in himself the affiliation with the two "homes", Slovenia and Australia, neither of which paradoxi-cally seems to in his poetry qualify as such any more in his poetry.
Keywords: Australia; Avstralija; diaspora; Slovenian migrant literature; slovenska izseljenska književnost; Žohar, Jože